Psychological interventions to improve academic motivation among first-year undergraduates in Nigeria - Victor Ayodeji Fehintola; Omolara O. Arewa; Hannatu Samaila (Academic Journal of Psychology and Counseling, 2026)
Academic motivation is important to students' success, yet many undergraduates have issues maintaining high levels of motivation throughout their studies. This study addressed the gap in research on effective interventions for enhancing academic motivation among undergraduate students in Oyo State, Nigeria. It investigated the effects of resilience skill training (RST) and goal-setting training (GST) with gender and academic self-efficacy as moderating variables. Using a quasi-experimental design with a 3x2x3 factorial structure, the research involved 59 university freshmen selected through multi-stage sampling. Two experimental groups (RST and GST) were compared with a control group, grounded in self-determination and social control theories. Validated instruments included the Academic Motivation Scale and the Academic Self-Efficacy Scale. Results demonstrated significant effects of interventions on academic motivation (F(2, 45) = 7.098, p = 0.002) and academic self-efficacy (F(2, 45) = 4.557, p = 0.016), while gender was not found to yield a significant effect (F(1, 45) = 1.206, p = 0.278). A significant two-way interaction emerged between intervention and academic self-efficacy (F(2, 45) = 3.837, p = 0.029). The study concludes that both RST and GST effectively enhance academic motivation among undergraduates. Key recommendations include integrating these interventions into university curricula and providing tailored interventions based on students' self-efficacy levels.